Adenosine Concentration in Patients With Neurally Mediated Syncope - Groppelli, Antonella; Brignole, Michele; Chefrour, Mohamed; Gastaldi, Marguerite; El Oufir, Farid; Deharo, Jean Claude; Parati, Gianfranco; Guieu, Régis (Frontiers in Cardiovascular Medicine, 2022)
Objective Either high or low values of adenosine blood level (ABL) can differentiate some forms of neurally-mediated syncope (NMS).. A rapid method of measurement, which can be used in clinical practice, has recently been developed. The aim of the present study was: 1) to compare ABLs in patients affected by NMS and in healthy controls; and 2) to assess the relative prevalence of low and high adenosine forms among an unselected syncope population. Methods Whole blood was collected after finger puncture and its concentration was measured by liquid chromatography /mass spectrometry (LC-MS/MS). The population consisted in unselected patients affected by NMS and healthy control subjects. Results Among 89 control subjects, the median ABL value was 0.54 µM (IQR 0.46-0.65). The lowest 5% and the upper 95% percentile were 0.40 and 0.80 µM respectively. Compared with healthy subjects, the 146 syncope patients showed on average a higher median ABL value (0.63 [IQR 0.45-0.73, p=0.04) and a larger distribution of values. Low ABL values below the 5th percentile were observed in 28 (19%) patients and in 5 controls, p=0.003 and high ABL values were observed in 26 (18%) patients and 5 controls, p=0.009. Conclusions ABL is different in patients with NMS than in healthy subjects. Patients with low and high adenosine values account for 19% and 18% of the general population affected by NMS. Thus, low and high ABL limits, as defined in this study, may help to screen syncope patients affected by NMS.